(untitled) - Kerr, E. Bartlett (New York, 1991)
Based on interviews with U.S. aircrews and other servicemen, as well as survivors of the attacks, this compelling account of America's assault on Japan's home islands tells how America delivered the decisive blow to the Japanese Empire--resulting in the destruction of 60 cities. Photographs.
Keywords: World war, 1939-1945,Japan; Aerial operations, american,History; Bombardment, 1944-1945